2007
DOI: 10.1197/j.aem.2007.05.013
|View full text |Cite
|
Sign up to set email alerts
|

Progression of Emergency Medicine Resident Productivity

Abstract: Objectives: To evaluate the progression in productivity of emergency medicine (EM) residents by postgraduate year, as measured by hourly work in relative value units (RVUs).Methods: This retrospective study was conducted at an Accreditation Council for Graduate Medical Education (ACGME)-accredited EM residency with a postgraduate year (PGY) 1-2-3 configuration. A query of an electronic billing database composed of more than 230,000 visits from academic years July 2003 to December 2006, representing at least fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 7 publications
1
18
0
Order By: Relevance
“…Previous studies have demonstrated a significant increase in productivity from first year to second year that may be associated with the rapid growth of the first-year residents as they become familiar with their new role as resident physicians and are able to see greater numbers of patients. 8 Furthermore, first-year residents in our department did not all rotate through the ED during both the control period and the study period.…”
Section: Methods Of Measurementmentioning
confidence: 99%
“…Previous studies have demonstrated a significant increase in productivity from first year to second year that may be associated with the rapid growth of the first-year residents as they become familiar with their new role as resident physicians and are able to see greater numbers of patients. 8 Furthermore, first-year residents in our department did not all rotate through the ED during both the control period and the study period.…”
Section: Methods Of Measurementmentioning
confidence: 99%
“…Clinical metrics derived from chart review or patient care information systems can be useful in assessing an individual's performance as measured by patients per hour, relative value units (RVUs), or other clinical care measures (e.g., patient acuity, resource utilization), 6,98 When linked to systematic and ongoing feedback, assessment of clinical metrics can lead to long-term clinical practice change. 6 While there is evidence that certain measures such as RVUs/hour correlate with individual cognitive assessments of multitasking ability, 99 they potentially suffer from a lack of specificity given the resident's inherent inability to practice independently because of his or her supervised role.…”
Section: Metricsmentioning
confidence: 99%
“…Prior research has indicated that higher training level is associated with greater resident PPH; however the effect on attending PPH has not been studied. 1,2,7,8 It may be that in a one-onone teaching model, despite senior residents seeing more patients than junior residents, the attending physician does not see proportionately more patients. The implications for an academic training center are unclear, as clinical productivity of attending physicians is only one of many parameters affecting attending reimbursement.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8] Four studies examined the difference in patients per hour for residents at varying post graduate training levels, and found a somewhat higher rate for each additional year of training. 1,2,7,8 Other studies examined the effect of learners on overall department throughput, and while one study found that residents slowed throughput, another found that residents had no impact, while medical students did not affect throughput in two studies. [3][4][5][6] No study to date has specifically examined the impact of learners on EM attending physician productivity, with regards to patients per hour (PPH).…”
Section: Impact Of Learners On Em Attending Physician Productivitymentioning
confidence: 99%